(untitled) (Bangladesh Heart Journal, 2021)
Background: The “obesity paradox”, a counterintuitive decrease in morbidity and mortality with increasing body mass index (BMI), has been shown in patients when acute cardiovascular decompensation occurs. However, whether this phenomenon exists in patients undergoing percutaneous coronary intervention (PCI) is not well known. The existence of obesity paradox and its impact on short-term clinical outcomes after PCI have not been thoroughly investigated, especially in Bangladesh. Methods: This cross-sectional observational study was conducted at National Institute of Cardiovascular Diseases, Dhaka, in 100 patients who underwent PCI. They were divided in two groups on the basis of BMI of Asian ethnicity: Group I (BMI < 23 kg/m2) and Group II (BMI <23.0 kg/m2). Short-term in-hospital outcomes after PCI were observed and recorded. Results: Acute left ventricular failure (LVF) was found to be statistically significant between groups (p < 0.01) being higher in Group-I. The difference of mean duration of hospital stay (LOS) after PCI was higher in the same group which was statistically significant (p < 0.01). Diabetes mellitus and dyslipidemia were found to be the independent predictors for developing adverse in hospital outcome (OR= 1.68 and 1.46; 95% CI = 1.25 – 2.24 and 1.16 – 1.83; p = 0.018 and 0.040, respectively). BMI was inversely associated with in-hospital outcomes after PCI (OR = 0.95; 95% CI = 0.91 – 0.98; p = 0.007). Conclusion: The results of the study uphold the phenomenon of the “obesity paradox” following PCI. The underweight and normal weight people are at greater risk to experience short-term in-hospital adverse clinical outcomes than overweight and obese people after PCI. Bangladesh Heart Journal 2021; 36(1): 1-8